Can treating vitamin D deficiency reduce exacerbations of chronic obstructive pulmonary disease?. (18th March 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: Jolliffe D, Greenberg L, Hooper R, Mathyssen C, Rafiq R, de Jongh R, Camargo C, Griffiths C, Janssens W, Martineau A. Vitamin D to prevent exacerbations of COPD: systematic review and meta-analysis of individual participant data from randomised controlled trials. Thorax 2019. doi:10.1136/thoraxjnl-2018-212092 . This project was funded by the National Institute for Health Research Health Technology Appraisal programme (project number 13/03/25). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000737/treating-vitamin-d-deficiency-may-reduce-exacerbations-of-copd